Penentu keputusan pembelian online: Peran mediasi kepuasan konsumen - Yanneri Elfa Kiswara Rahmantya; Retnaning Tyas; Nuri Purwanto; Odang Supiatna; Herma Wiharno (Jurnal Manajemen Maranatha, 2026)
Engagement with digital content and celebrity endorsers can encourage individuals to make purchases, but it does not necessarily guarantee long-term repeat buying and customer satisfaction. In the fashion industry, this challenge is particularly noticeable, which Instagram has become a key marketing tool. A local fashion brand, Erigo, actively uses Instagram as a powerful tool to communicate consumer behavior and its brand values. Using a model-based analytical approach, this research examines both indirect and direct effects of celebrity endorsers, information quality, and brand image on purchasing decisions. This research uses a quantitative design with purposive sampling, involving 130 respondents who have previously purchased products from Erigo on Instagram. An online survey and variance-based structural equation model (VBSEM) are used to collect and analyze the data, respectively. The results of this research demonstrate that online purchase decisions (OPD) are positively influenced by celebrity endorsers (CE), information quality (IQ), and brand image (BI). However, these decisions are not affected by customer satisfaction (CS). CE shows an insignificant effect on CS; however, the positive influence of IQ and BI, on CS, is significant. Interestingly, CS mediates the effect of CE on OPD, but it does not mediate the effect of IQ and BI on OPD. These findings imply that a marketer's powerful personality can create strong emotional connections that extend beyond simple post-purchase evaluations. By highlighting the importance of customer satisfaction in shaping social media-driven purchasing decisions, this research contributes to the fields of digital marketing and consumer behavior, particularly in the Indonesian fashion industry. By offering a more complex understanding of how endorsement effects operate, this research contributes to the literature by going beyond traditional models that primarily use customer satisfaction as a mediator in the consumer behavior field.